2020
DOI: 10.1371/journal.pone.0243824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitroxin and arbuscular mycorrhizal fungi on the agro-physiological traits and grain yield of sorghum (Sorghum bicolor L.) under drought stress conditions

Abstract: The use of bio-fertilizers in agro-ecosystems is considered to have the potential to improve plant growth in extreme environments featuring water shortages. However, while arbuscular mycorrhizal fungi (AMF) and bacteria bio-fertilizers have been used in other plants to enhance stress tolerance, little is known about their symbiotic effect on sorghum (Sorghum bicolor L.) growth under drought stress conditions. Therefore the aim of this study was to investigate the inoculation of sorghum with Nitroxin and Glomus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 68 publications
(73 reference statements)
2
6
0
1
Order By: Relevance
“…Soluble protein is an essential osmoregulation substance and nutrient in plants that can alleviate ion imbalances and physiological droughts caused by salt and drought stress [54], which is involved in the stress resistance of plants. In this study, the soluble protein content in the leaves of the treatment groups were significantly higher than that in CK group, which is consistent with the result of a previous study [49,55]. Furthermore, other studies revealed that the increase in the leaf soluble protein content of plants can be caused by the increase of nitrate reductase enzyme activity, higher nitrogen fixation, and growth hormone production through AM fungi and microbial fertilizer application [56,57].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Soluble protein is an essential osmoregulation substance and nutrient in plants that can alleviate ion imbalances and physiological droughts caused by salt and drought stress [54], which is involved in the stress resistance of plants. In this study, the soluble protein content in the leaves of the treatment groups were significantly higher than that in CK group, which is consistent with the result of a previous study [49,55]. Furthermore, other studies revealed that the increase in the leaf soluble protein content of plants can be caused by the increase of nitrate reductase enzyme activity, higher nitrogen fixation, and growth hormone production through AM fungi and microbial fertilizer application [56,57].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, other studies revealed that the increase in the leaf soluble protein content of plants can be caused by the increase of nitrate reductase enzyme activity, higher nitrogen fixation, and growth hormone production through AM fungi and microbial fertilizer application [56,57]. CAT, POD, and SOD in the plants can reduce membrane lipid peroxidation, maintaining and protecting the stability of the cell membrane structure and function [55]. In this study, the activities of CAT, POD, and SOD in the treatment groups were all significantly higher than that in CK, especially in the Mi group, which had the highest POD activity among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMF establish an extensive hyphal network with the plant root system, particularly fine root hairs, enhancing accessibility to a larger soil surface area and water retention. Bernardo et al [ 35 ] reported that Funneliformis mosseae -inoculated wheat exhibited improved WUE under water limitation, while Kamali and Mehraban [ 36 ] observed similar results in sorghum inoculated with Glomus mosseae . Furthermore, AMF contribute to enhanced N and P contents in maize and wheat by exploring solution-filled soil pores inaccessible to plant roots and facilitating nutrient uptake [ 34 , 37 ].…”
Section: Building Resilience: Harnessing Mycorrhizal Symbiosis For En...mentioning
confidence: 98%
“…Application of microbes-based bio-fertilizers in agro-ecosystems is beneficial for plant growth and yield enhancement in both conventional ( Kalayu, 2019 ) and extreme environments ( Kamali and Mehraban, 2020 ; Rizvi et al, 2020 ). Among microbial formulations, the research on PSMs impacting growth, crop nutrition, and yield of cereal crops under greenhouse/field trials are quite large ( Table 4 ).…”
Section: Psm-sorghum Interactions: Inoculation Effects On Growth Crop Nutrition and Grain Yieldmentioning
confidence: 99%